2016
DOI: 10.1021/acs.est.5b06349
|View full text |Cite
|
Sign up to set email alerts
|

Brine Spills Associated with Unconventional Oil Development in North Dakota

Abstract: The rapid rise of unconventional oil production during the past decade in the Bakken region of North Dakota raises concerns related to water contamination associated with the accidental release of oil and gas wastewater to the environment. Here, we characterize the major and trace element chemistry and isotopic ratios ((87)Sr/(86)Sr, δ(18)O, δ(2)H) of surface waters (n = 29) in areas impacted by oil and gas wastewater spills in the Bakken region of North Dakota. We establish geochemical and isotopic tracers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
183
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(189 citation statements)
references
References 28 publications
5
183
1
Order By: Relevance
“…Quantifying cumulative landscape‐level effects is a challenge that other researchers have dealt with and that we attempted to address via the development of our disturbance index (Cote et al , Craig et al ). Although we observed minimal landscape‐level effects of oil and gas disturbance on brood abundance, development also has the potential to effect waterfowl at much smaller scales in the form of increased water contamination (Preston and Chesley‐Preston , Lauer et al ) and reduced invertebrate diversity that are crucial for brood development (Preston et al ). These factors could accumulate over time to have broadly deleterious effects on waterfowl productivity if females with broods do not avoid wetlands with reduced water or invertebrate quality.…”
Section: Discussionmentioning
confidence: 83%
“…Quantifying cumulative landscape‐level effects is a challenge that other researchers have dealt with and that we attempted to address via the development of our disturbance index (Cote et al , Craig et al ). Although we observed minimal landscape‐level effects of oil and gas disturbance on brood abundance, development also has the potential to effect waterfowl at much smaller scales in the form of increased water contamination (Preston and Chesley‐Preston , Lauer et al ) and reduced invertebrate diversity that are crucial for brood development (Preston et al ). These factors could accumulate over time to have broadly deleterious effects on waterfowl productivity if females with broods do not avoid wetlands with reduced water or invertebrate quality.…”
Section: Discussionmentioning
confidence: 83%
“…() were not able to conclude that energy development activities in the Bakken production area affected groundwater quality; however, Gleason and Tangen () and Lauer et al . () observed that surface‐water and/or groundwater samples collected in the Bakken region had elevated levels of inorganic contaminants associated with the produced water (or brine) from the Bakken oil and gas wells. Recently, Horner et al .…”
Section: Introductionmentioning
confidence: 81%
“…Heavy metals have been introduced to soil through agricultural management, such as the addition of composts (Sharifi & Renella, 2015), fertilizers (Chen et al, 2014) and pesticides (Morgan, 2013), industrial activities (Gottesfeld et al, 2018;Khaledian, Pereira, Brevik, Pundyte & Paliulis, 2017), mining (Mbila & Thompson, 2004), poorly regulated or illegal recycling of electronic wastes or e-wastes (Wu et al, 2015) and the construction of structures using treated timber or lumber (Gardner, Weindorf & Flynn, 2013). The petroleum industry can negatively affect soil near oil or water production and spill sites or near waste disposal locations with a wide range of organic chemicals, heavy metals (Laffon, Pásaro & Valdiglesias, 2016), salts (Lauer, Harkness & Vengosh, 2016) and naturally occurring radioactive materials (NORM) (Zielinski & Otton, 1999). Organic chemicals have been added to soil through agricultural and industrial activities and waste disposal, including the discarding of pharmaceutical wastes (Burgess, 2013).…”
Section: Highlightsmentioning
confidence: 99%